Proof of concept and feasibility of the app-based '#SWPMoveMore Challenge': Impacts on physical activity and well-being in a police population. (March 2022) - Oliver, Helen; Thomas, Owen; Copeland, Robert James; Hesketh, Ian; Jukes, Matt; Chadd, Kathryn; Rocca, Marc
An app-based physical activity intervention (#SWPMoveMore Challenge) was completed by 239 workers from one UK police force using a quasi-experimental design. Impacts were assessed against minutes of movement, individual difference and work-related stress variables using quantitative and qualitative approaches. The concept was feasible and translatable to a UK police population and the intervention significantly benefited direct measures of physical activity and perceptions of vitality, job stress, job satisfaction, negative coping strategy use and engagement at work. The intervention was also motivational in helping individuals take-up and maintain physical activity and positively impacted morale and comradery within the work-force.